2016
DOI: 10.1021/acs.jpca.6b03538
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of meso-Substituted Porphyrins: The Role of Cation Radicals to the Half-Wave Oxidation Potential Splitting

Abstract: In this study, the electrochemical behavior of free base and zinc meso-substituted porphyrins is examined by cyclic voltammetry (CV) and density functional theory (DFT). The results show that the half-wave oxidation potential splitting of the two oxidation states (ΔE= second E1/2 - first E1/2) of tetraphenylporphyrin (H2TPP) and its zinc complex (ZnTPP) are higher than those of porphyrins and their zinc complexes with meso-substituted five-membered heterocylic rings. The ΔE values follow the trend of TPP > T(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…However, the zero-field splitting (zfs) between the two unpaired electrons of Ni renders the metal EPR silent at the X band (9.5 GHz), 19,60 and again, we only observe the TEMPO radical. The spectrum of 3(Cu) show an additional multiplet at a lower field because of hyperfine coupling of the copper unpaired electron with the four porphyrin 14 N nuclei, which is characteristic of copper porphyrins. 61,62 Time-Resolved Spectroscopy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the zero-field splitting (zfs) between the two unpaired electrons of Ni renders the metal EPR silent at the X band (9.5 GHz), 19,60 and again, we only observe the TEMPO radical. The spectrum of 3(Cu) show an additional multiplet at a lower field because of hyperfine coupling of the copper unpaired electron with the four porphyrin 14 N nuclei, which is characteristic of copper porphyrins. 61,62 Time-Resolved Spectroscopy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…13 Porphyrins can also exist as stabile oxidized, reduced, or neutral radicals. 14 From a biological perspective, extensive research on oxophlorin and mesohydroxyporphyrin has been carried out to elucidate their role in the catabolism of heme. 15 Inspired by Nature, impressive synthetic achievements have been made in the design and realization of stable porphyrin oxyl radicals with relevant magnetic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological systems present microheterogeneity, caused by the coexistence of microphases such as aqueous polar and highly hydrophobic lipid. 64,65 Therefore it is relevant to study the physicochemical properties of sensitizers at different media. We have studied the electrochemical behavior of (2) using cyclic voltammograms (CV) in four different solvents.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…We have found that the effect of porphyrin ring deformation on the half-wave oxidation potential splitting (Δ E = second E 1/2 – first E 1/2 ) values of the free base prophyrins is less than the effect of sterically controlled π-conjugation of the meso -phenyl groups to the central porphyrin ring, defined by the dihedral angles (ψ) between meso -phenyl groups and porphyrin ring. Recently, we have published a study on zinc porphyrins with meso -substituted five-membered heterocylic rings . We found that Δ E can be easily predicted by calculating the spin density distribution of zinc porphyrin cation radicals on meso -carbon positions.…”
Section: Introductionmentioning
confidence: 99%